2015
DOI: 10.1159/000431356
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Antiplatelet Therapy Trial after the FDA Update: Noncardiovascular Deaths, Cancer and Optimal Treatment Duration

Abstract: Background: The landmark Dual Antiplatelet Therapy (DAPT) trial revealed an impressive reduction of stent thrombosis and myocardial infarction after prolonged 30-month DAPT compared to the conventional 12-month regimen. However, aside from the expected extra bleeding risks, more cancers and noncardiovascular deaths (NCVD) were observed in the 30-month DAPT arm. Objective: We aimed to comprehend the totality of DAPT trial evidence in the light of the FDA medical review. Results: A significant excess of solid ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 2 publications
4
15
0
Order By: Relevance
“…The differences in PLATO and PEGASUS cancer-related outcomes are presented atTable 3. The PEGASUS consistent with the DAPT trial results(14) exhibiting similar to prasugrel or clopidogrel extra cancer risks after ticagrelor beyond 1 year therapy(15).Sepsis:Despite more common infections after ticagrelor, PLATO reported surprising reduction in deaths due to sepsis with 7 (0.1%) after ticagrelor versus 23 fatalities (0.2%) after clopidogrel(2). In contrast, PEGASUS revealed a trend towards more infection/sepsis-related deaths after ticagrelor (n=31) than after aspirin (n=24) (RR=1.29; 95%CI 0.76 -2.20, p=0.35)(10).…”
supporting
confidence: 54%
“…The differences in PLATO and PEGASUS cancer-related outcomes are presented atTable 3. The PEGASUS consistent with the DAPT trial results(14) exhibiting similar to prasugrel or clopidogrel extra cancer risks after ticagrelor beyond 1 year therapy(15).Sepsis:Despite more common infections after ticagrelor, PLATO reported surprising reduction in deaths due to sepsis with 7 (0.1%) after ticagrelor versus 23 fatalities (0.2%) after clopidogrel(2). In contrast, PEGASUS revealed a trend towards more infection/sepsis-related deaths after ticagrelor (n=31) than after aspirin (n=24) (RR=1.29; 95%CI 0.76 -2.20, p=0.35)(10).…”
supporting
confidence: 54%
“…The alarming data that such an approach may be associated with increased cancer incidence forced re-analysis of the main trials from this point of view [ 29 31 ]. The adverse effects of antiplatelet therapy were first observed during the TRITON trial in which prasugrel versus clopidogrel was assessed in patients with acute coronary syndromes and for vorapaxar treatment in the TRACER trial [ 30 ]. Ticagrelor treatment (reversibly binding oral P2Y12 receptor blocker) assessed in the PEGASUS trial was also associated with significant excess in cancer death [ 132 ].…”
Section: Adp Receptorsmentioning
confidence: 99%
“…Ticagrelor treatment (reversibly binding oral P2Y12 receptor blocker) assessed in the PEGASUS trial was also associated with significant excess in cancer death [ 132 ]. DAPT therapy from a 30-month trial with prasugrel and clopidogrel provided abundant data [ 30 ]. This trial revealed that a long-term antiplatelet approach is associated with cancer development that contributes to about half of noncardiovascular deaths (NCVD).…”
Section: Adp Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the possible role of platelets in promotion of malignant diseases and metastatic spread, effects of anti-platelet therapy on metastasis have been intensively studied in animal models [ 3 , 6 , 7 ] as well as in humans. Today there is overwhelming evidence from epidemiological studies [ 8 12 ] and clinical trials [ 13 , 14 ] that supports the involvement of platelets in metastatic spread.…”
Section: Introductionmentioning
confidence: 99%